2006
DOI: 10.1086/501348
|View full text |Cite
|
Sign up to set email alerts
|

The Fundamental Plane for z = 0.8-0.9 Cluster Galaxies

Abstract: We present the fundamental plane (FP) for 38 early-type galaxies in the two rich galaxy clusters RX J0152.7Ϫ1357 ( ) and RX J1226.9ϩ3332 ( ), reaching a limiting magnitude of in z p 0.83 z p 0.89 M p Ϫ19.8B the rest frame of the clusters. While the zero-point offset of the FP for these high-redshift clusters relative to our low-redshift sample is consistent with passive evolution with a formation redshift of , the FP for z ≈ 3.2 form the high-redshift clusters is not only shifted as expected for a mass-indepen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
157
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(180 citation statements)
references
References 26 publications
21
157
1
1
Order By: Relevance
“…Several papers have mentioned that the intrinsic dispersion of the FP is small (∼0.1 dex) (Kjaergaard et al 1993;Jørgensen et al 1996;Kelson et al 1997;Jørgensen et al 1999;Blakeslee et al 2002;Bernardi et al 2003c;Reda et al 2005;Jørgensen et al 2006), although other studies demonstrate that the intrinsic dispersion is far from being small (∼0.3 dex) (Bender et al 1992;La Barbera et al 2003;Nigoche-Netro et al 2009). This dispersion causes the galaxy distribution in the space defining the FP to follow a surface whose width is determined by this dispersion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers have mentioned that the intrinsic dispersion of the FP is small (∼0.1 dex) (Kjaergaard et al 1993;Jørgensen et al 1996;Kelson et al 1997;Jørgensen et al 1999;Blakeslee et al 2002;Bernardi et al 2003c;Reda et al 2005;Jørgensen et al 2006), although other studies demonstrate that the intrinsic dispersion is far from being small (∼0.3 dex) (Bender et al 1992;La Barbera et al 2003;Nigoche-Netro et al 2009). This dispersion causes the galaxy distribution in the space defining the FP to follow a surface whose width is determined by this dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, their results conflict with those of other authors. For example, Treu et al (2005), Jørgensen et al (2006), and Fritz et al (2009) find that the zero point of the FP depends on redshift but that the slope of the FP is steeper for higher redshift galaxies than for galaxies in the local Universe. They interpret this as a mass dependence of the star formation history, that is, the low-mass galaxies (10 10.3 M ) have experienced star formation as recently as z form ∼ 1.1, while, galaxies with masses ∼10 10.8 M and masses >10 11.3 M had their last major star formation episode at z form > 1.25 and z form > 1.6 (Jørgensen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Since the galaxy M/L depends on both the star formation history of the galaxies and the cosmology, the study of the FP is a valuable tool for studying the evolution of the stellar population in early-type galaxies. Several studies of intermediate (z ∼ 0.3) and high-redshift (z ∼ 0.85) clusters of galaxies have used the ZP shift of the plane to estimate the average formation redshifts of stars in early-type galaxies (e.g., Bender et al 1998;van Dokkum et al 1998;Jørgensen et al 1999;Kelson et al 2000;van Dokkum & Stanford 2003;Wuyts et al 2004;Jørgensen et al 2006). In general, they have all found values compatible with a redshift formation greater than 3.…”
Section: Introductionmentioning
confidence: 99%
“…These differences manifest themselves as an evolution in the FP coefficient α at increasing redshift, from 1.2 (in the B band) at redshift 0.0 to 0.8 at z ∼ 0.8−1.3 (van der Wel et al 2004;Treu et al 2005a,b;van der Wel et al 2005;di Serego Alighieri et al 2005;Holden et al 2005;Jørgensen et al 2006). However, this change in the slope has not been observed at 0.2 < z < 0.8 (e.g., van Dokkum & Franx 1996;Kelson et al 2000;Wuyts et al 2004;van der Marel & van Dokkum 2007b;MacArthur et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of the intrinsic dispersions in the FJR and the KR have not been studied thoroughly because a third variable is believed to cause most of the intrinsic dispersion in both these relations. The intrinsic dispersion in the FP has been barely studied because, it has been assumed to be small (∼0.1 dex, Kjaergaard et al 1993;Jørgensen et al 1996;Kelson et al 1997;Jørgensen et al 1999;Blakeslee et al 2002;Bernardi et al 2003c;Reda et al 2005;Jørgensen et al 2006). However, some studies have found that the intrinsic dispersion is far from small (∼0.3 dex, Bender et al 1992;La Barbera et al 2003;Nigoche-Netro et al 2009).…”
Section: Introductionmentioning
confidence: 99%